Microbes associated with spontaneous cacao fermentations - A systematic review and meta-analysis - Alexander J. Taylor; Eduardo Cardenas-Torres; Michael J. Miller; Sihai Dave Zhao; Nicki J. Engeseth (Current Research in Food Science, 2022)
Chocolate is a product of the fermentation of cacao beans. Performed on-farm or at local cooperatives, these are spontaneous cacao fermentations (SCFs). To better understand SCFs, this study sought to identify SCF microbes, their interrelationships, and other key parameters that influence fermentation. This is important because differences in fermentation can have an impact on final product quality. In this study, a systematic data extraction was performed, searching for literature that identified microbes from SCFs. Each unique microbe, whether by location or by fermentation material, was extracted from the articles, along with parameters associated with fermentation. Data were collected and analyzed for three interactions: microbe-to-geography, microbe-to-fermentation method, and microbe-to-microbe. The goal was to attribute microbes to geographical locations, fermentation materials, or to other microbes. Statistically significant relationships will reveal target areas for future research. Over 1700 microbes (440 unique species) were identified across 60 articles. The top three countries represented are Brazil (22 articles, n = 612 microbes), the Ivory Coast (14 articles, n = 237), and Ghana (10 articles, n = 257). Several countries were far less, or never represented, and should be considered for future research. No specific relationship was identified with microbes to either geographical location or fermentation method. Using a Presence-Absence chart, 127 microbe-to-microbe interactions were identified as statistically significant. Data extraction into SCF research has revealed major gaps of knowledge for the cacao microbiome. By better understanding the cacao microbiome, researchers will be able to identify key microbes and fermentation parameters to better influence the fermentation.